Cannosphaeropsis quattraocchiae, a new species of dinoflagellate cyst from the mid Cenozoic of the Colorado Basin, Argentina - Guerstein, Gladys Raquel (2001)
Cannosphaeropsis quattrocchiae n. sp., from the Cenozoic of the Colorado Basin, resembles two other species, Cannosphaeropsis utinensis and Cannosphaeropsis passio, and has been confused with the former. However, separation of the three species, based in part on the location of the processes, allows for their use in refining Cenozoic stratigraphy and paleoecology. On present evidence, the last appearance datum of Cannosphaeropsis quattrocchiae appears to be early Miocene, whereas Cannosphaeropsis passio is known only from the mid Miocene. Cannosphaeropsis utinensis, primarily a late Cretaceous species, occurs occasionally in lower Paleocene sediments. Geographically, Cannosphaeropsis utinensis and Cannosphaeropsis passio are known only from the Northern Hemisphere, whereas Cannosphaeropsis quattrocchiae is known only from the Southern Hemisphere.